Caracterização de asfaltenos e subfrações por espectrometria de massas de Ionização e dessorção à laser (LDI-MS) - Fonseca, Victor da Rocha (2023)
Currently, one of the major problems in the oil industry is the deposition of asphaltenes, which can occur throughout the production chain. This occurs due to their tendency to aggregate and precipitate when exposed to physical-chemical variations, thus causing major impacts and economic losses for the industries involved. In addition, the preparation of increasingly uniform samples, in terms of composition and physical-chemical properties, is carried out through the application of fractionation methods, enabling a more effective study of these complex compounds. The study and elucidation of the behaviors and chemical characteristics of asphaltenes are of utmost importance for the development of treatments capable of preventing or mitigating this deposition generated. The Laser Desorption Ionization (LDI) technique coupled with mass spectrometry (MS) emerges as a viable option for the characterization of asphaltenes. In view of this scenario, general concepts related to the characterization of asphaltenes and their subfractions, as well as the evolution of their structural models and the application of mass spectrometry with emphasis on the LDI-MS ionization technique will be addressed in this state of the art.